2008
DOI: 10.1002/mrc.2242
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation and complete NMR spectral assignments of four new diterpenoids from Smallantus sonchifolius

Abstract: Four new diterpenoids, named smaditerpenic acid A-D, together with five known compounds, were isolated from the H(2)O extract of the leaves of Smallantus sonchifolius (yacon) cultivated in Liaoning, China and their structures were elucidated on the basis of one- and two-dimensional NMR (including (1)H, (13)C-NMR, (1)H-(1)H COSY, HSQC, TOCSY, HMBC, and ROESY), electrospray ionization mass spectrometry (ESI-MS), and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…434.1) have been isolated from leaves of yacon cultivated in China [5][6][7]. In continuation of this work, we found that smallanthaditerpenic acids (SA) A, B, C and D possessed stronger inhibitory activity of a-glucosidase than that of caffeic acid, which had been regarded as the major component possessing this property [8].…”
mentioning
confidence: 99%
“…434.1) have been isolated from leaves of yacon cultivated in China [5][6][7]. In continuation of this work, we found that smallanthaditerpenic acids (SA) A, B, C and D possessed stronger inhibitory activity of a-glucosidase than that of caffeic acid, which had been regarded as the major component possessing this property [8].…”
mentioning
confidence: 99%
“…Diterpenoids and melampolides derivates were isolated from yacon (Consolacion, Ragasa, Alimboyoguen, & Dennis, 2008;Karin, Irmgard, & Fernando, 2007;Katerina & Jitka, 2003;, which has a physiological role in the pest-resistant and antimicrobial activity of this plant (Kakuta, Seki, Hashidoko, & Mizutani, 1992;Lin, Hasegawa, & Kodama, 2003). Polyunsaturated fatty acids (PUFAs), smallanthaditerpenic acids and octadecatrienoic acids were isolated from the leaves of yacon cultivated in China (Dou, Tian, & Qiu, 2008;Xiang, Gai, Dou, & Kang, 2009), which possesses a potential ability of antidiabetes. Other components, such as saccharides and essential oils were also confirmed in yacon (Katerina & Jitka, 2003).…”
mentioning
confidence: 99%
“…The following compounds were found in the leaves: an antifungal melampolide, 8-angeloyl-1(10),4,11(13)-germacuratrien-12,6-olid-14-oic acid methyl ester, named sonchifolin, and three known melampolides, polymatin B, uvedalin and enhydrin (Inoue et al 1995 ); protocatechuic (2.5 and 0.12 mg/g), chlorogenic (9.9 and 1.7 mg/g), caffeic (14.7 and 0.09 mg/g) and ferulic (traces) acids ; six sesquiterpene lactones, 8β-tigloyloxymelampolid-14-oic acid methyl ester, 8β-methacryloyloxymelampolid-14-oic acid methyl ester, sonchifolin, uvedalin, enhydrin and fl uctuanin (Lin et al 2003 ); chlorogenic, caffeic and ferulic acid, isomers of dicaffeoylquinic acid, an unidentifi ed derivative of chlorogenic acid, fl avonoid quercetin and an unidentifi ed fl avonoid (Simonovska et al 2003 ); four diterpenoids named smaditerpenic acid A-D and fi ve known compounds (Dou et al 2008b ); ent -kaurane-3β,16β,17,18-tertol, 3 R ,7 E -9-butoxylmegastigma-3-ol-3-O -β-D -glucopyranoside, 3 S ,5 R ,6Z-megastigma-6-en-3,5,8,9-tertol and fi ve known compounds octacosanol, 3′,4′,5-trihydroxy-3,7-dimethoxyfl avone, 3,4-dihydroxybenzaldehyde, isorhamnetin and ent -kaurane-3β,16β,17-triol (Qiu et al 2008 ); ent -kaurenoic acid (Ragusa et al 2008 ); smallanthaditerpenic acid A, smallanthaditerpenic acid B, smallanthaditerpenic acid C, smallanthaditerpenic acid D, ent -kaurane-3β, 16β, 17, 19-tetrol and ent -kaurane-16β, 17, 18, 19-tetrol (Dou et al 2008a ); gallic acid, β-sitosterol, behenic acid, kaempferol, quercetin, vanillic acid and hexadecanoic acid (Xie et al 2008 ); two new melampolide-type sesquiterpene lactones, 8β-epoxyangeloyloxy-9α-ethoxy-14-oxo-acanthospermolide and 8β-angeloyloxy-9α-ethoxy-14-oxo-acanthospermolide along with 11 known melampolide allo-schkuhriolide, enhydrin, polymatin A, fl uctuanin, 8β-angeloyloxy-9α-acetoxy-14-oxo-acanthospermolide, 8β-angeloyloxy-14-oxo-acanthospermolide, 8β-methacryloyloxymelampolid-14-oic acid methyl ester, uvedalin, polymatin B, 8β-tigloyloxymelampolid-14-oic acid methyl ester and sonchifolin (Hong et al 2008 ); octadecatrienoic acid elucidated as 13( R )-hydroxy-octadeca-(9 E ,11 E ,15 Z )-trienoic acid and a benzyl glycoside elucidated as benzyl alcohol 7-O -α-L -arabinopyranosyl(1″→2′)-β-D -glucopyranoside, along with a known compound 13( R )-hydroxy-octadeca-(9 Z ,11 E ,15 Z )-trienoic acid (Xiang et al 2009 ); smallanthaditerpenic acids A, B, C and D and chlorogenic and caffeic acids ( Xiang et al 2010b ); two diterpenes, named ent -kaurane-3β, 16β,17, 19-tetrol and entkaurane -16β,17,18,19-tetrol (Dou et al 2010 ); a hexenol glycoside elucidated as Z -hex-3-en-1-ol O -α-L -arabinopyransyl (1″→2′)-β-D -glucopyranoside and two known compounds ent -15β-hydroxy-kaur-16-en-19-oic acid and ent-18-hydroxy-kaur-16-en-19-oic acid (Xiang et al 2010a ); caffeic, chlorogenic and three dicaffeoylquinic acids and enhydrin (Genta et al 2010 ); two ...…”
Section: Leaf and Stem Phytochemicalsmentioning
confidence: 99%